Alaninaminotransferase and specific viral hepatitis markers in the blood of donors - Zh. K. Burkitbayev; G. A. Yesenbayeva; S. A. Abdrakhmanova; Zh. Zh. Bibekov; Ye. B. Zhiburt (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study the dynamics of viral hepatitis detection rate after implementation of donors preliminary testing for alanine aminotransferase (ALT) activity. Material and methods. Viral hepatitis markers detection rate by immuno-chemiluminescence assay at testing for ALT activity in venous (n=47080) and capillary (n=22530) blood of donors was studied. Results. Males had higher ALT activity in comparison to that in females, both in venous (for 54.1%), and in capillary (for 27.2%) blood. ALT capillary blood activity was higher on the average, than in venous, for 10.1% in men and 33.3% in women. Conclusions. ALT activity elevation is associated by twofold increase in the rate of lacteous serum and more frequent detection of hepatitis serological markers. In the samples received after capillary blood culling the anti-hepatitis C virus antibodies positivity rate was decreased. No relation of ALT activity to results of parenteral virus genomes screen was revealed.